Tingkat pengetahuan tentang bantuan hidup dasar (BHD) pada pengemudi kendaraan umum Kota Medan: Studi kuasi-eksperimental - Lubis, Andriamuri Primaputra; Irina, Rr Sinta; Akbar, Hera Zein; Elfazi, Tazzya Shailla (Poltekkes Kemenkes Aceh, 2025)
Background: Basic Life Support (BLS) knowledge is essential, particularly for public transport drivers who frequently encounter medical emergencies. Adequate education on BLS can enhance their preparedness in responding to such situations.Objectives: This study aims to assess the level of knowledge among public transport drivers in Medan City regarding BLS before and after an educational interventionMethods: This study employed a quasi-experimental design using a one-group pretest-posttest approach. The sample consisted of 521 public transportation drivers in Medan City, divided into four groups: angkot drivers (125), online motorcycle taxi drivers (201), motorized rickshaw drivers (125), and rental car drivers (50). Data were collected using a structured questionnaire containing items assessing basic knowledge of Basic Life Support (BLS), administered both before and after an educational intervention. Data were analyzed descriptively to summarize respondent characteristics, and paired t-tests and Chi-Square tests were used to assess statistical differences in knowledge scores before and after the intervention and between driver groups.Results: The majority of participants were male (n = 451, 86.56%), with the most common age range being 31–40 years (n = 250, 47.98%). Most respondents had completed junior high school (n = 251, 47.98%), and the largest driver category was online motorcycle taxi drivers (n = 201, 38.57%). The initial assessment indicated that most participants had a limited understanding of BLS. However, post-intervention analysis demonstrated a statistically significant improvement, with the majority achieving higher knowledge scores in the posttest.Conclusion: Educational interventions on Basic Life Support significantly enhance the knowledge levels of public transport drivers in Medan City, as evidenced by the substantial difference between pretest and posttest scores.